2019
DOI: 10.1002/app.47553
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of compatibilizers for blends of polypropylene carbonate and polybutylene succinate via free‐radical grafting of maleic anhydride

Abstract: This study focuses on creating an optimal grafting compatibilizer for blends of polypropylene carbonate (PPC) and polybutylene succinate (PBS). PPC and PBS were blended separately with different amounts of maleic anhydride (MAH) and with and without dicumyl peroxide (DCP) to aid the free-radical grafting. Titration analysis evidenced that MAH reacted with the polymers terminal groups and backbones using free-radical functionalization. Thermogravimetric analysis (TGA) and gas permeation chromatography (GPC) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…One is that the melt grafting requires much less time, around tens of minutes, than hours in solution or vapor phase grafting . The other is that melting grafting achieves the modification of polymer bulk, more efficient than the only surface modification in solution grafting and vapor phase grafting . There are few reports on the melt grafting modification of materials by plasma‐induced polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…One is that the melt grafting requires much less time, around tens of minutes, than hours in solution or vapor phase grafting . The other is that melting grafting achieves the modification of polymer bulk, more efficient than the only surface modification in solution grafting and vapor phase grafting . There are few reports on the melt grafting modification of materials by plasma‐induced polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Also, dissolution studies on the same samples showed that there was no crosslinking in the system due to the DCP action. Moreover, the amount of potential inner chain grafting was assumed to be very small based on the NMR results found in the previous work . Termination by disproportionation was considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…This process involves the thermal decomposition of the peroxide into free radicals that can abstract hydrogens from the polymer backbone to induce reaction with MAH. Also, maleic anhydride can undergo esterification reaction with the OH groups of PPC leaving maleic acid end groups, which can further react in the system and also make PPC more thermally stable …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations